Potensi Escherichia Coli Sebagai Resistansi Antibiotik - Yunda Safitri; Wirda Resinta Gultom; Dwita Ardana L. Tobing; Dicky Rayza Sianturi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This literature review examines the increase in antibiotic resistance in Escherichia coli, a Gram-negative bacterium that frequently causes infections in humans and animals. Although most E. coli strains are harmless, some pathogenic strains have shown resistance to various antibiotics, posing a significant challenge in the healthcare field. This study highlights the various resistance mechanisms found in E. coli, including the production of β-lactamase enzymes that can inactivate antibiotics, modification of antibiotic targets, changes in membrane permeability, and increased activity of efflux pumps that expel antibiotics from bacterial cells. Additionally, this review discusses factors contributing to the spread of resistance, such as the excessive and inappropriate use of antibiotics in medicine and livestock, and the transfer of resistance genes through mobile genetic elements. The literature highlights recent research efforts to address this issue, including the development of new antibiotics, the use of antibiotic combinations, and alternative therapies such as bacteriophages and specific enzyme inhibitors. This review emphasizes the importance of strict surveillance and prudent antibiotic use policies to prevent the further spread of antibiotic resistance in E. coli, ensuring the effectiveness of bacterial infection treatments in the future.